60.2k views
3 votes
Find the remainder of (h^4+h^2-2)/(h+3)

1 Answer

6 votes


(-3)^4+(-3)^2-2=88, so by the polynomial remainder theorem, the remainder is 88.

To verify this, we can compute the quotient remainder:


h^4=h^3\cdot h, and
h^3(h+3)=h^4+3h^3. Subtracting from the numerator gives a remainder of
-3h^3+h^2-2


-3h^3=-3h^2\cdot h, and
-3h^2(h+3)=-3h^3-9h^2. Subtracting from the previous remainder gives a new remainder of
10h^2-2.


10h^2=10h\cdot h, and
10h(h+3)=10h^2+30h. Subtracting from the previous remainder gives a new remainder of
-30h-2.


-30h=-30\cdot h, and
-30(h+3)=-30h-90. Subtracting from the previous remainder gives a new remainder of
88, which doesn't contain factors of
h, so we're done.

This means we have


(h^4+h^2-2)/(h+3)=h^3-3h^2+10h-30+(88)/(h+3)

User Oob
by
5.1k points